Classificação e caracterização de maciços rochosos no âmbito da mineração - CUNHA, Harlem Enckel Souza (2019)
Methods of classifications of rock masses are good tools to assess and quantify the quality of a rock mass and assist in engineering projects in rock, such as excavations, opening galleries and tunnels, slope stability, and various other interventions that have the stuff, the rock. These methods quantify or describe in terms of numbers several characteristics of the rock mass. The main classification systems already developed as classification geomechanics RMR (Rock Mass Rating) have widespread use around the world, which ultimately promote the development of own rating system and other tools linked to it, such as the emergence of empirical formulas for determining the mechanical properties of rock masses. This paper seeks to use three classification systems, the RMR (Rock Mass Rating), Q-system (Tunnelling Quality Index) and GSI (Geological Strength Index), for classification of rock masses and therelationship of field analysis and geological interpretations indicating the geomechanical characterisation.The results of these ratings and characterizations, as well as suggest a series of geological engineering procedures, can also be used to calculate some mechanical properties of rock masses by means of empirical formulas developed by some authors, often based on correlation of a large number of practical studies arising from the use of these parameters generated so many in the rankings and massive Rocky characterizations. Based on this study, we seek to understand the various relationships between ratings and characterization of rock masses and their mechanical properties, as well as conclusions on the use of certain equations and methods involved in these processes.